IMPACT OF DIFFERENT INTRADIALYTIC EATING TIMES ON HEMODYNAMIC STABILITY AND HEMODIALYSIS ADEQUACY - Setiowati, Tutut; Rosyid, Fahrun Nur; Kristinawati, Beti (Universitas Aisyah Pringsewu, 2025)
Intradialytic eating (IE) remains controversial due to the absence of standardised clinical guidelines. While it can potentially improve patients' nutritional status, its effects on hemodynamic stability and dialysis adequacy remain inconclusive. This study aimed to evaluate the impact of IE timing on hemodynamic and dialysis adequacy. A quasi-experimental design with a control group was employed, involving 32 hemodialysis patients assigned to either an intervention or control group. The intervention group received a standardised meal consisting of 100 ml of milk and two egg whites (200 kcal; approximately 15 grams of protein) at varying times during five dialysis sessions. Observed parameters included systolic and diastolic blood pressure, pulse rate, MAP, and Kt/V. Measurements were recorded every 30 minutes throughout each session. Data were analysed using independent t-test and Repeated Measures ANOVA with Bonferroni correction. No statistically significant differences between the intervention and control groups across all parameters (p 0.05). However, within the intervention group, repeated measures ANOVA revealed changes in systolic blood pressure (p = 0.004), MAP (p = 0.021), and Kt/V (p = 0.031). Post-hoc Bonferroni tests identified significant differences in systolic blood pressure (p = 0.010 and p = 0.045) and MAP (p = 0.041). IE had a significant impact on hemodynamics during the first and second hours of dialysis (p 0.05). These findings indicate that IE toward the end of dialysis may serve as a safe nutritional approach, with minimal hemodynamic risk and greater potential for preserving dialysis adequacy compared to earlier phases of the session